2017
DOI: 10.1002/cjce.22946
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of cinnamaldehyde using Pd catalysts supported on Mg/Al mixed oxides: Influence of the Pd incorporation method

Abstract: A series of hydrotalcite-like compounds was synthesized by varying Mg/Al molar ratio with values of 2, 3, and 4. After thermal treatment at 823 K, the corresponding mixed oxides were obtained and used as catalytic supports. The incorporation of a Pd metallic phase (0.5 g/g loading), was carried out by two methods: 1) in situ vapour phase thermal decomposition, and 2) impregnation by organic method. Fresh and calcined samples were characterized by XRD and N 2 sorption experiments. The basic and metal functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The Pd/La 2 O 2 CO 3 ‐TNS catalyst exhibits a TOF of 41 238 h −1 in contrast to 1251 h −1 for the Pd/La 2 O 2 CO 3 ‐NR. This is one of the highest activities for reported heterogeneous hydrogenation catalysts, such as Pd@TNT, Pd‐NMC, PdWN/SBA‐15, and so on . This result indicated that the morphology effect of the La 2 O 2 CO 3 support can modify the reaction rate of CAL hydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…The Pd/La 2 O 2 CO 3 ‐TNS catalyst exhibits a TOF of 41 238 h −1 in contrast to 1251 h −1 for the Pd/La 2 O 2 CO 3 ‐NR. This is one of the highest activities for reported heterogeneous hydrogenation catalysts, such as Pd@TNT, Pd‐NMC, PdWN/SBA‐15, and so on . This result indicated that the morphology effect of the La 2 O 2 CO 3 support can modify the reaction rate of CAL hydrogenation.…”
Section: Resultsmentioning
confidence: 99%